FITUR DESAIN PADA APLIKASI ZOOM SEBAGAI PENDUKUNG KONSULTAN ARSITEKTUR DI ERA PANDEMI - Ni Kadek Yuni Utami; Nyoman Gema Endra Persada (Jurnal Anala, 2022)
Since 2020, the Covid-19 pandemic has made “work from home” regulation implemented in almost all Indonesian companies to prevent the transmission of the virus among workers. Companies including architectural consultants then use online video conference applications such as Zoom to support coordination in work in the pandemic era. Architectural consultants used into conventional methods such as direct discussions, sketches, or drawing discussion with printed documents are then required to adapt to online media. The purpose of this study is to determine the design features of the Zoom application that are able to support the productivity of architectural consulting firms. This research provides information for architecture consultants to find out the types of design features can be used during online conferences. The method in this study is a descriptive qualitative, where the researcher observes the use of the Zoom on an architectural consultant and analyzes its suitability with the needs of an architectural consultant. This research shows that design features in the Zoom application such as screen share, whiteboard and file sharing are effective to help architectural consulting firms work in the pandemic era.